Identity, Youth, and Crisis - Erikson, Erik H. (Erik Homburger), 1902-1994 (New York W.W. Norton & Company INC, 1968)
Essays in ego psychology, based on papers written from 1951 to 1967, by a neo-Freudian analyst and theorist.
Includes Index and Notes.
Keywords: Identity (Psychology) -- Youth--Psychology -- Adolescent psychology